Scenarios Analysis of Stratospheric Ozone Concentrations – Box Modeling and Statistical Inference - Chen, Jiang (International Journal of Computer Science and Information Technology, 2024)
This study uses a method that combines box models and statistical inference to deeply explore the interaction between stratospheric ozone concentration and nitrogen oxides (NOx) and chlorine compounds (ClOx). Ordinary differential equations written in MATLAB were used to simulate chemical reactions in the atmosphere. Based on these results, evaluate qualitatively the effects of NOx and ClOx on ozone concentration by further multiple linear regression analysis using VIF for multicollinearity detection and AIC for model selection. Results show that NO2 and N2O5 have significant effects on the variations of O3, while Cl is related to the content of another species. The developed fast simulator can quickly process complex chemical reaction equations and meteorological data to predict future ozone concentration changes. The research not only enhances understanding of atmospheric chemical dynamics but also helps inform environmental policy.